Підвищення ефективності верстатних систем управлінням критичними параметрами процесу обробки - Пестунов, В. М.; Лисенко, О. В.; Pestunov, V.; Lysenko, О. (КНТУ, 2005)
У статті розглядаються верстатні системи, які реалізують можливість управління критичними параметрами процесу обробки для підвищення ефективності цих систем, а саме розширення технологічних можливостей, поліпшення якості обробки та підвищення продуктивності. In the article the machine-tool systems realizing possibility of management by the critical parameters of process of treatment for the rise of efficiency of these systems are examined, namely expansion of technological possibilities, improvements of quality of treatment, rises of productivity.
Increasing the efficiency of machine tool systems by controlling critical machining process parameters
Keywords: технологічна система верстата; верстатна система; автоматичне управління; критичні параметри; technological system of the machine tool; machine tool system; automatic control; critical parameters